2022
DOI: 10.1002/mp.15859
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study of seed spots analysis to characterize dose and linear‐energy‐transfer effect in adverse event initialization of pencil‐beam‐scanning proton therapy

Abstract: Background: Both dose and linear energy transfer (LET) could play a substantial role in adverse event (AE) initialization of cancer patients treated with pencil-beam-scanning (PBS) proton therapy. However, not all the voxels within the AE regions are directly induced from the dose and LET effect. It is important to study the synergistic effect of dose and LET in AE initialization by only including a subset of voxels that are dosimetrically important. Purpose: To perform exploratory investigation of the dose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…In the iterative treatment planning process between the dosimetrist, physicist and physician, the beam angles were modified and the number of beams increased to optimize target coverage, minimize organ at risk dose including lowering biological dose and improve plan robustness by adding beams and adjusting beam angles, as is done with CIRT treatment planning. The plans included in this study represent what the treating physician determined to be the best clinical plan for the patient for optimal target coverage and sparing of organs at risk considering physical and biological dose [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Using fewer beams or more standard beam angles resulted in inferior treatment plans which were not accepted by the treating physician.…”
Section: Methodsmentioning
confidence: 99%
“…In the iterative treatment planning process between the dosimetrist, physicist and physician, the beam angles were modified and the number of beams increased to optimize target coverage, minimize organ at risk dose including lowering biological dose and improve plan robustness by adding beams and adjusting beam angles, as is done with CIRT treatment planning. The plans included in this study represent what the treating physician determined to be the best clinical plan for the patient for optimal target coverage and sparing of organs at risk considering physical and biological dose [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Using fewer beams or more standard beam angles resulted in inferior treatment plans which were not accepted by the treating physician.…”
Section: Methodsmentioning
confidence: 99%
“…The opensource fast MC code, MCsquare (2,17,18,20,43) has been thoroughly validated against other MC codes and measurements in both phantoms and patient geometries (2,18,(43)(44)(45)(46)(47)(48)(49). In addition, MCsquare has been fully commissioned and has been incorporated into our in-house treatment planning system, Shiva (6,19,(50)(51)(52)(53)(54)(55), and has been clinically used as the second monitor unit (MU) check system at our proton center for years (2,18) and other proton centers (56). Therefore, we chose MCsquare in this study as a fast Monte Carlo dose and linear energy transfer (LET) calculation engine.…”
Section: Methodsmentioning
confidence: 99%
“…The adverse events after PBT are more complex than photon therapy due to the unique non-linear characteristic of the relationship of RBE with dose and LET d in PBT. 6,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] A newly developed tool, dose-LET d volume histogram (DLVH), was developed and was able to correlate high LET d and high dose with rectal adverse events. 26,28 It was reported that high LET d (≥2.5 keV/µm) volume in the rectum might result in a higher incidence rate of grade≥2 (CACTE V4.0) rectal bleeding in prostate cancer patients treated with proton therapy, even though the corresponding dose volume was moderate.…”
Section: Introductionmentioning
confidence: 99%
“…Dose averaged LET (LET d ) is relevant in planning study because it is a physical parameter that can be scored through Monte Carlo methods. The adverse events after PBT are more complex than photon therapy due to the unique non‐linear characteristic of the relationship of RBE with dose and LET d in PBT 6,8,10–27 . A newly developed tool, dose‐LET d volume histogram (DLVH), was developed and was able to correlate high LET d and high dose with rectal adverse events 26,28 .…”
Section: Introductionmentioning
confidence: 99%